TÓLEPBERGEN QAYÍPBERGENOV POVESTLERINDEGI SYUJET TIPLERI - Sársenbaev, Q.J. (SCIENCE and SOCIETY, 2025)
The article analyzes the features of the plot in the works of the famous writer T.Kayipbergenov. The object of the study was the writer's narratives. Based on examples, the types of plots in stories and their use were studied, and scientific conclusions were drawn.
Keywords: writer; novels; plot; plot types; skill; description; character